Factors Associated with the Prevalence of Thyroid Nodules and Goiter in Middle-Aged Euthyroid Subjects - Dauksiene, Dalia (Int J Endocrinol, 2017)
The aim of the present study was to determine associations of thyroid hormone levels and different metabolic parameters and anthropometric measurements with volume of nodular and nonnodular thyroid as well as with prevalence of goiter and thyroid nodules in middle-aged euthyroid subjects. Methods. The study consisted of 317 euthyroid subjects aged 48-49 from the Kaunas Cardiovascular Risk Cohort study. Thyroid-stimulating hormone (TSH), free thyroxine (FT4), and antithyroid peroxidase antibody (ATPO) levels, as well as anthropometric and metabolic parameters and smoking information, were evaluated. Results. In subjects with and without thyroid nodules, thyroid volume correlated with components of metabolic syndrome, body mass index (BMI), smoking, and TSH levels. In the nonnodular thyroid group, thyroid volume was also positively related to serum insulin and HOMA-IR, whereas a negative correlation between thyroid volume and leptin was identified in the nodular thyroid group. The goiter was identified in 12.3% of subjects. Female gender, thyroid nodules, smoking, BMI, and levels of TSH were independent predictors for goiter. Thyroid nodules were found in 31.2% of participants. Female gender, higher TSH levels, and thyroid volume were independent risk factors for thyroid nodules. Conclusions. Female gender, thyroid nodules, smoking, BMI, and TSH levels were identified as potential predictors of goiter. Female gender, TSH levels, and thyroid volume predicted the presence of thyroid nodules.